Breaking from orthodoxy: The effects of social disorganization on perceived burglary in nonmetropolitan communities - Cancino, Jeffrey M. (American journal of criminal justice, 2003)
The present research breaks from the urban orthodoxy and tests two ecological propositions in less densely populated, nonmetropolitan communities. The analysis file features 1,125 citizens nested in 31 residential units located in Michigan. Hierarchical logistic modeling is used to examine the effects of structural antecedents and social mechanisms, net of citizen-level correlates, on perceived burglary. Three findings emerge: 1) respondents living in residential units with higher levels of economic disadvantage report that burglary is significantly more problematic in their community; 2) social cohesion is inversely associated with perceived crime; and 3) social cohesion partially mediates the effect of economic disadvantage.